Importance of Mesoporous Silica Particle Size in the Stabilization of Amorphous Pharmaceuticals-The Case of Simvastatin - Knapik-Kowalczuk, Justyna; Kramarczyk, Daniel; Chmiel, Krzysztof; Romanová, Jana; Kawakami, Kohsaku; Paluch, Marian (MDPI, 2020)
In this paper, the role of mesoporous silica (MS) particle size in the stabilization of amorphous simvastatin (SVT) is revealed. For inhibiting recrystallization of the supercooled drug, the two MS materials (Syloid((R)) XDP 3050 and Syloid((R)) 244 FP) were employed. The crystallization tendency of SVT alone and in mixture with the MS materials was investigated by Differential Scanning Calorimetry (DSC) and Broadband Dielectric Spectroscopy (BDS). Neither confinement of the SVT molecules inside the MS pores nor molecular interactions between functional groups of the SVT molecules and the surface of the stabilizing excipient could explain the observed stabilization effect. The stabilization effect might be correlated with diffusion length of the SVT molecules in the MS materials that depended on the particle size. Moreover, MS materials possessing different particle sizes could offer free spaces with different sizes, which might influence crystal growth of SVT. All of these factors must be considered when mesoporous materials are used for stabilizing pharmaceutical glasses.
Důležitost velikosti částic mezoporézní siliky pro stabilizaci amorfních léčiv - Případ Simvastatin
Keywords: simvastatin; amorphous pharmaceuticals; mesoporous silica; stabilization; recrystallization; simvastatin; amorfní léčiva; mezoporézní silika; stabilizace; rekrystalizace